2017
DOI: 10.1002/joc.5219
|View full text |Cite
|
Sign up to set email alerts
|

Circulation type classifications for temperature and precipitation stratification in Italy

Abstract: During the last few decades, weather circulation type classifications (CTCs) have been widely used to gain insight into processes at the synoptic scale, but also for studying the relationship between atmospheric circulation and surface climate variability. This study aims to evaluate the best performing CTCs based on COST733 software for the stratification of daily ground-level precipitation and surface air temperature across Italy by means of four statistical metrics. Six classification methods belonging to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 44 publications
0
29
1
Order By: Relevance
“…The valley is crossed by a number of tributaries running down from the Alps in the north and from the Apennines in the south. As reported by the Koppen classification, the Po Valley has a humid subtropical climate (Cfa), with the conformation of the plain causing a high level of relative humidity, increasing from south to east (Vallorani et al, 2018). Winters are cool, and the mean temperature recorded during the 1971-2010 reference period ranges between 1 C and 4 C. Temperature inversion is common during the cold period when the height of the Planetary Boundary Layer (PBL) rarely exceeds 450 m. Summers are hot, and temperatures range between 22 C and 25 C (1971( , Bigi et al, 2012.…”
Section: Introductionmentioning
confidence: 99%
“…The valley is crossed by a number of tributaries running down from the Alps in the north and from the Apennines in the south. As reported by the Koppen classification, the Po Valley has a humid subtropical climate (Cfa), with the conformation of the plain causing a high level of relative humidity, increasing from south to east (Vallorani et al, 2018). Winters are cool, and the mean temperature recorded during the 1971-2010 reference period ranges between 1 C and 4 C. Temperature inversion is common during the cold period when the height of the Planetary Boundary Layer (PBL) rarely exceeds 450 m. Summers are hot, and temperatures range between 22 C and 25 C (1971( , Bigi et al, 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Text files of the two circulation type classifications (pct9 and san9) and the centroid values of MSLP and 500HGT (Fig. 2) are available to the following DOI (https://doi.org/10.5281/zenodo.1321007, Vallorani and Messeri, 2018). The pct9 and san9 classifications were selected through a sensitivity analysis detailed in a specific study (https://doi.org/10.1002/joc.5219, Vallorani et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Then such classifications were compared through the use of proper statistical indexes in order to assess the stratification of the ground-level precipitation and the surface air temperature across Italian peninsula. The PCT (Principal Component Transversal) and the SAN (Simulated Annealing) methods with 9 classes computed on MSLP and 500HGT (Vallorani et al, 2018) were selected as the best performing classifications for precipitation and temperature respectively (see in Fig. 2 the centroid maps for PCT09 and SAN09 classifications as a result of the calibration module, where the centroids are the central value of the class/cluster).…”
Section: Methodsmentioning
confidence: 99%
“…A thorough review of CTCs can be found in Ramos et al (2015). Many works have addressed the relation between CTCs and rainfall (Bartoszek and Skiba, 2016;Casado et al, 2010;Jacobeit et al, 2017;Maheras et al, 2018;Raziei et al, 2013), temperature (Maheras et al, 2006;Kyselý and Huth, 2008), or both variables (Jacobeit et al, 2009;Vallorani et al, 2018). Some works analyse the impact of the CTs in different high mountain areas like the Pyrenees (Esteban et al, 2005), the Alps (Masson and Frei, 2014;Panziera et al, 2015) or the Himalayas (Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%